2015
DOI: 10.1002/eat.22446
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of the consequences and social functions of fat talk in friendship groups

Abstract: These findings indicate that fat talk is a mechanism through which the thin ideal is transmitted between individuals. Interventions at the level of the friendship group to challenge norms and communication styles may break the link between societal risk factors and individual risk of eating disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 35 publications
3
27
0
1
Order By: Relevance
“…Similar to findings on adolescent girls’ attempts to avoid peer rejection, several studies on fat talk have revealed that young women sense expectations to participate in fat talk when observing friends engaging in fat talk (Cruwys et al, 2016; Martz et al, 2009). Cruwys et al examined relationships among fat talk, thin-ideal internalization, and dieting intentions using an experimental design, where they manipulated fat talk in participants’ actual friendship groups.…”
Section: Introductionsupporting
confidence: 63%
“…Similar to findings on adolescent girls’ attempts to avoid peer rejection, several studies on fat talk have revealed that young women sense expectations to participate in fat talk when observing friends engaging in fat talk (Cruwys et al, 2016; Martz et al, 2009). Cruwys et al examined relationships among fat talk, thin-ideal internalization, and dieting intentions using an experimental design, where they manipulated fat talk in participants’ actual friendship groups.…”
Section: Introductionsupporting
confidence: 63%
“…The thin‐body ideal may be transmitted in a peer group through so‐called ‘fat talk’. Engaging in fat talk is associated with both higher social acceptance—provided the peer‐group norm is pro‐fat talk—and increased correlates of disordered eating (Cruwys, Leverington, & Sheldon, ). Whether this process underlies the relationship between social acceptance and eating pathology in our study is a question for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Assigning value to a stimulus is contingent upon context: a highly palatable food may be experienced as less palatable in a social context in which people are discussing the stigma associated with weight gain [18]. AN typically onsets in early adolescence, a developmental period in which interoceptive states are increasingly elaborated by social contexts [19, 20].…”
Section: Introductionmentioning
confidence: 99%